Insetos na escola: compartilhando novos aprendizados - HENN, Yara Fernanda Ferreira (Universidade Federal do Oeste do Pará, 2023)
Insects are the largest animal group on the planet, representing approximately 3/4 of the biological diversity of the animal kingdom. They are a group of extreme ecological and economic importance, interfering directly in the lives of human beings. Unfortunately, insects are often viewed with repugnance because some species are associated with the transmission of diseases or garbage. In this aspect, the school plays an essential role in demystifying and explaining insects to students, who can also act as replicators of knowledge. In this paper we present partial results of the previous knowledge of 6th and 7th grade students about insects and the results of playful practices on insects to complement the traditional teaching in school. The results indicate a lack of knowledge about insects, but show students' interest in obtaining knowledge about this group and in participating in dynamic and playful activities that can enhance traditional classes.